Halal and Ṭayyib Governance in Indonesia's Free Nutritious Meal Programme: A Halal Supply Chain Perspective from South Sulawesi - Muh Zaitun Ardi; Abdul Rashid Khan; Nadyatul Hikmah Shuhufi; Muhammad Shuhufi; Fatmawati; Mau’idhatul Hasanah Ridwan; Ahmed Medi (MUI Sulawesi Selatan, 2026)
The Free Nutritious Meal Programme (MBG), as a national public food policy, has been examined predominantly from nutritional, public health, and socio-economic perspectives, while the dimension of ḥalāl–ṭayyib governance across the entire supply chain remains largely underexplored. This gap is significant because ḥalāl–ṭayyib assurance constitutes an essential component of Muslim consumer protection and public welfare within the framework of Maqāṣid al-Sharīʿah. This study aims to analyse the implementation of ḥalāl–ṭayyib governance in the MBG supply chain in South Sulawesi, identify critical ḥalāl control points throughout the upstream and downstream supply chain, and develop an integrated ḥalāl governance model for public food programmes. Employing a multi-site qualitative case study with a socio-legal approach, the research draws upon in-depth interviews, non-participant observations, and document analysis conducted in Makassar, Gowa, Maros, and Bone Regencies. The data were analysed using the interactive model of Miles, Huberman, and Saldaña through systematic coding and thematic analysis. The study adopts the ḥalāl supply chain, the ḥalāl assurance system, and Maqāṣid al-Sharīʿah as integrated analytical frameworks. The findings reveal substantial governance deficiencies, reflected in inadequate supplier ḥalāl certification, limited ḥalāl traceability, insufficient ḥalāl audit mechanisms, risks of cross-contamination in Satuan Pelayanan Pemenuhan Gizi (SPPG) kitchens, and the absence of integrated ḥalāl logistics and digital monitoring systems. Furthermore, the programme has significantly contributed to ḥifẓ al-nafs, ḥifẓ al-ʿaql, and ḥifẓ al-nasl through improved nutritional fulfilment and human development. However, ḥifẓ al-dīn remains inadequately safeguarded due to the absence of a comprehensive and systematic ḥalāl assurance framework. The principal contribution of this study is the development of an Integrated Ḥalāl–Ṭayyib Governance Model for Public Food Programmes, which integrates the ḥalāl supply chain, the ḥalāl assurance system, and Maqāṣid al-Sharīʿah within a comprehensive public food governance framework. The study advances the literature by extending ḥalāl governance beyond the commercial food industry into the domain of Islamic public food governance. It also offers practical policy recommendations by emphasising the importance of digital ḥalāl traceability, risk-based ḥalāl governance, and institutional coordination among the National Nutrition Agency (BGN), the Badan Penyelenggara Jaminan Produk Halal (BPJPH), the Majelis Ulama Indonesia (MUI), local governments, and supply chain stakeholders to strengthen sustainable ḥalāl public food governance.